Advances in plant male sterility for hybrid seed production: an overview of conditional nuclear male sterile lines and biotechnology-based male sterile systems - Vasupalli, Naresh; Mogilicherla, Kanakachari; Shaik, Vahab; Rao, K. R. S. Sambasiva; Bhat, Shripad R.; Lin, Xinchun (Frontiers in Plant Science, 2025)
Male sterility forms the foundation of hybrid seed production technology in field crops. A variety of genetically controlled male sterility/fertility systems starting with cytoplasmic male sterility (CMS), genic male sterility (GMS) including conditional male sterility and transgenic-based male sterility have been developed and deployed for heterosis breeding over the past century. Here we review environment-sensitive genic male sterility (EGMS) and biotechnology-based male sterility systems and describe the underlying molecular mechanisms. Advances in crop genomics and discovery of a large number of nuclear genes governing anther/pollen development, which are shared across species, are helping design diverse types of male sterile lines suitable for different crop species and situations. In particular, gene editing offers quick and easy route to develop novel male sterility systems for hybrid seed production. We discuss the advantages and challenges of biotechnology-based male sterility systems and present alternative strategies to address concerns of transgenics. Finally, we propose development of functional male sterility systems based on pollen competition as the future area that holds great promise for heterosis breeding.